Improved Performance of GaAs-based Terahertz Emitters - Headley, C; Fu, L; Parkinson, P; Xu, X; Lloyd-Hughes, J; Jagadish, C; Johnston, M; IEEE (2010)
We have improved the stability and performance of terahertz photoconductive (Auston) switches using a combination of (NH4)2S surface passivation and silicon nitride (Si3N4) encapsulation. The passivation and encapsulation processes increased the average terahertz power generated four-fold.